Study of Certain Biochemical Attributes of Pantja Buck Semen (Indian Journal of Animal Production and Management, 2024)
The current study was conducted to study biochemical attributes of Pantja Buck semen. For this  purpose six mature healthy bucks were selected from the Goat Unit maintained at Department of  Livestock Production Management, College of Veterinary and Animal Sciences, Pantnagar,  Uttarakhand (India). All the experimental bucks were kept under similar feeding and management  conditions. Semen collection was done early morning by artificial vagina method. Total 36 semen  samples were collected for a period of 3 months. Immediately after the collection, samples were  examined for biochemical attributes. Overall mean value of pH was found (6.61 ± 0.02) independent  of buck age. Resazurin and Methylene blue reduction time were noted higher for younger bucks and  minimum for older bucks with overall value 3.15 ± 0.25 and 6.04±0.36 min. respectively. Mean values  of HOST and Millovanov’s resistance test were recorded as 36.10 ± 1.17 % and 5216.70 ± 1.94  respectively. 16.76 ± 0.86 % sperms were found resistance to cold shock.
Keywords: Biochemical attributes; Pantja buck; Semen